THREE-DIMENSIONAL MODEL PRINTING IN ORAL AND MAXILLOFACIAL RECONSTRUCTIVE SURGERY: COMPARISON OF THREE-DIMENSIONAL MODELS AND MULTISLICE COMPUTED TOMOGRAPHY SCANS - Latief, Adhitya; Suhardi, Pradono; Badri, Cholid (International Journal of Applied Pharmaceutics, 2018)
Objective: The objective of this study is to compare fabrication of commonly used three-dimensional (3D) models with original multislice computed tomography (MSCT) scan data for accuracy and precision in reconstruction surgery. Methods: MSCT data from 10Â samples are processed and manufactured to be 3D models. Both groups are then measured and analyzed for the purpose of comparison. Results: The average mandibular measurement difference between 3D models and MSCT scans is 0.26Â mm more <2%. The final results of the comparison reveal high accuracy in 3D models compared to MSCT scan data. Conclusion: The 3D model could be considered as surgical guidance for maxillofacial reconstruction surgery since it yields highly accurate results.